Effect of anharmonicities in the critical number of trapped condensed atoms with an attractive two-body interaction - Filho, Victo S. [UNESP]; Gammal, Arnaldo [UNESP]; Tomio, Lauro [UNESP] (American Physical Society (APS), 2002)
We determine the quantitative effect, in the maximum number of particles and other static observables, due to small anharmonic terms added to the confining potential of an atomic condensed system with negative two-body interaction. As an example of how a cubic or quartic anharmonic term can affect the maximum number of particles, we consider the trap parameters and the results given by Roberts et al. [Phys. Rev. Lett. [Formula Presented] 4211 (2001)]. However, this study can be easily transferred to other trap geometries to estimate anharmonic effects. © 2002 The American Physical Society.